International Murre Conservation Strategy and Action Plan (Conservation of Arctic Flora and Fauna (CAFF), Arctic Environment, 1996)
Murres are particularly vulnerable to the direct or indirect effects of a range of human activities, such as hunting, tourism, oil pollution, competition with fisheries and entrapment in fishing gear, due to characteristics of their behaviour and distribution, their ecological position in marine systems, and their traditional use for human food. These threats are common throughout most of the their range, and they have resulted in significant population declines in several circumpolar countries during the present century. Many murre populations are shared by two or more circumpolar countries as a result of their migration and dispersal patterns, so both exploitation and conservation actions in one country can have significant effects in others. Effective conservation of these economically and ecologically important species therefore requires a coordinated international approach, as provided for through the framework of CAFF. The goal of this strategy and action plan is: To facilitate circumpolar implementation of initiatives to conserve, protect and restore murre populations in the Arctic. Facilitate circumpolar implementation of initiatives to conserve, protect and restore murre populations in the Arctic.